Intimate Partner Violence Survivors and Pets: Exploring Practitioners' Experiences in Addressing Client Needs. Issue 2 (April 2018) - Hageman, Tina O'Neil; Langenderfer-Magruder, Lisa; Greene, Tamara; Williams, James Herbert; St. Mary, Jason; McDonald, Shelby Elaine; Ascione, Frank R.
Research has documented a relationship between intimate partner violence (IPV) and animal abuse. Literature reports that many times IPV survivors delay seeking safety because of their concern for the safety of their pets and many shelters do not provide services for their pets. There continues to be a need for evidence-based guidelines to address the needs of survivors and their pets. This exploratory study documents the experiences of IPV practitioners from community agencies serving families impacted by IPV. Focus groups were conducted identifying four overarching themes: (1) pets as members of the family, (2) inconsistencies regarding screening practices, (3) need for comprehensive safety planning, and (4) safe housing for both survivors and their pets. Implications for research, practice, and policy are discussed.